2008
DOI: 10.1007/s11999-008-0194-7
|View full text |Cite
|
Sign up to set email alerts
|

Do Patient Expectations of Spinal Surgery Relate to Functional Outcome?

Abstract: It is important for surgeons to understand patients' expectations for surgery. We asked whether patient factors and preoperative functional outcome scores reflect the degree of expectations patients have for posterior spinal surgery. Second, we asked whether patients' expectations for surgery predict improvements in functional outcome scores after surgery. We prospectively enrolled 155 consecutive surgical patients with greater than 90% followup. Patients' expectations were evaluated preoperatively along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 19 publications
(34 reference statements)
7
106
2
3
Order By: Relevance
“…The finding that gender, BMI, previous back surgery, leg pain intensity, comorbidities, pain in the thoracic spine, somatization, treatment expectations, and walking distance were predictive of spinal surgery referral is in line with previous studies showing that they are also indicative of spinal surgery outcome [12,[19][20][21][22][23]. This can be interpreted as that surgeons are aware of and adhere to some extent to the current literature and (international) guidelines.…”
Section: Comparison With the Literaturesupporting
confidence: 88%
“…The finding that gender, BMI, previous back surgery, leg pain intensity, comorbidities, pain in the thoracic spine, somatization, treatment expectations, and walking distance were predictive of spinal surgery referral is in line with previous studies showing that they are also indicative of spinal surgery outcome [12,[19][20][21][22][23]. This can be interpreted as that surgeons are aware of and adhere to some extent to the current literature and (international) guidelines.…”
Section: Comparison With the Literaturesupporting
confidence: 88%
“…7 The expectations of patients, their characteristics, and assessments of psychosocial factors should be integrated into any treatment plan for lumbar canal stenosis, as these can determine which patients will benefit from the proposed surgical treatment. 24,25 In our study, like that of Mannion et al, 20 after being questioned about expectations, 40% of patients were overly optimistic, considering the improvement of the following items: leg pain, walking ability, independence in daily activities, and mental well-being. This percentage increased to 50% when evaluating the results related to sports activities, back pain, social contacts, and physical ability.…”
Section: Discussionsupporting
confidence: 63%
“…These results were similar to those reported in other studies. 7,24 Diseases of the cervical or lumbar spine have a large impact on both the physical and mental HRQoL domains. The disabilities caused by diseases negatively impact the HRQoL and are associated with a high prevalence of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the predictive power of psychological variables is also supported by our finding that patients planning to receive early post-operative rehabilitation with a biopsychosocial approach are predicted to have less prospective functional disability levels than patients receiving traditional post-operative exercise therapy. Previous studies that have included pre-surgical outcome expectations in multivariate models have found its predictive significance when testing pain, functional and HRQOL-related outcomes [5,20,29,33,39,48]. Our results showed that patient's expectations of future back pain-related outcome was the most important predictor of prospective HRQOL, but was not predictive of pain or functional related outcomes.…”
Section: Discussionmentioning
confidence: 46%
“…Many possible reasons for mixed lumbar fusion surgery outcomes exist, including instrumentation failure, inadequate surgical technique and poor patient selection. Factors previously suggested to be predictive of pain and disability-related outcomes include pre-surgical pain/function [42], negative personality traits [19,31,40,41,44], emotional status [41], anxiety/depression [3,23,28,40,41], fear avoidance (FA) beliefs [28], negative outcome expectations [20,48] negative coping [3], smoking status [41], gender [9], exercise [9], litigation [23], duration of back pain and workers' compensation [3,19,40,41].…”
Section: Introductionmentioning
confidence: 99%